Osteology and radiology of the vertebral column in the white-eared opossum (Didelphis albiventris) - Inamassu, Letícia Rocha [UNESP]; Schimming, Bruno Cesar [UNESP]; Dadalto, Carmel Rezende [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2020)
The white-eared opossum present a higher roadkill number in Brazil, and the vertebral column is often affected when some type of trauma occurs. Thus, this study describes the osteology and radiology of the vertebral column in white-eared opossum to serve as a basis for support in the veterinary clinical care, since the casuistry of care of this marsupial has increased every year. Radiographs of the cervical (C), thoracic (T), lumbar (L), sacral (S) and caudal (Cd) segments of the vertebral column were taken in thirty-five white-eared opossums (Didelphis albiventris). Furthermore, ten opossums without evident vertebral acquired or congenital abnormalities at the radiographic study were selected for anatomical study. Osteology was correlated with the radiographic images. The use of radiographs allowed the identification of congenital and acquired vertebral changes, as well as the identification of anatomical structures, their distribution and morphology and the number of vertebrae. The vertebral formula varied in the white-eared opossum. In 27 of 35 white-eared opossums (77.2%) with normal vertebral morphology, three vertebral formulas were observed: C7/T13/L6/S2 (62.9%), C7/T13/L5/S2 (5.7%) and C7/T13/L7/S2 (8.6%). Most of the specimens presented 27 caudal vertebrae. The anticlinal vertebra was identified as T10 in 77.2% and T11 in 22.8% of opossums. Cervical block vertebra was observed in two animals and sacrocaudal block vertebra in one animal. The haemal arches could be seen from Cd3–Cd4 in 80% and Cd2–Cd3 in 20% of opossums. The white-eared opossum showed a slender vertebral column with a relatively short thoracic region, a relatively long lumbar region and a highly flexible lumbosacral transition, suggesting that this animal is a fast-running and agile opossum. Therefore, these findings may serve as a basis for further research and support the veterinary clinical care, since the casuistry of care for this marsupial has increased every year.
Keywords: anatomy; marsupial; radiology; spine; wild animals